Boosting the coagulation restores haemostasis in ticagrelor-treated mice. Issue 8 (December 2016) - Pehrsson, Susanne; Hansson, Kenny; Nelander, Karin; Nylander, Sven
Abstract : Antiplatelet therapy is given to patients with acute coronary syndrome to reduce the risk for thrombotic events, but may increase the risk for bleeding. Ticagrelor was administered intravenously to mice. Cumulative blood loss and bleeding time were measured after cutting 5 mm of the tail, 20 min after the start of ticagrelor infusion. The tail was placed in a hemoglobin-sensitive device measuring light absorbance (abs) over time for 35 min. Activated recombinant human factor VII (rhFVIIa; NovoSeven; NovoNordisk A/S, Bagsvaerd, Denmark) 1 mg/kg (study 1); recombinant human prothrombin (rhFII, MEDI8111) 10 mg/kg (study 2); or vehicle was given intravenously once bleeding had commenced, within 90s after tail cut. Ticagrelor resulted in more than 98% inhibition of ex-vivo ADP-induced platelet aggregation. In study 1, the median blood loss in the ticagrelor, vehicle, and rhFVIIa groups were 909, 122, and 397 abs*s, respectively ( P  < 0.05 for both comparisons, including the ticagrelor group). Similar pattern was seen for bleeding time. The median bleeding time in the ticagrelor, vehicle, and rhFVIIa groups were 2003, 449, and 884s, respectively ( P  < 0.05 for both comparisons, including the ticagrelor group). In study 2, the median blood loss and bleeding time in the ticagrelor group were 362 abs*s and 1847s. The corresponding numbers for the vehicle and rhFII groups were 71 abs*s and 613s, and 178 abs*s and 701s, respectively ( P  < 0.05 for comparisons between ticagrelor and vehicle for both blood loss and bleeding time). In mice dosed to complete P2Y12 inhibition, boosting coagulation by administration of rhFVIIa or rhFII within 90s after bleeding initiation can partly reverse ticagrelor-enhanced bleeding.